Crystal structure of bis(bipyridine)bis(1,3,5-benzenetricarboxylato)- tricadmium(II) monohydrate, Cd3(C10H8N2)2(C9H3O6)2 · H2O - Zhang, Jing; He, Di-Ping; Ng, Seik Weng (De Gruyter Open, 2011)
C38H24Cd3N4O13, monoclinic, C12/cl (no. 15), a = 23.700(5) Å, b = 11.688(1) Å, c = 20.563(5) Å, β = 135.16(4)°, V = 4016.5 Å3, Z = 4, Rgt(F) = 0.044, wRref(F2) = 0.145, T= 293 K. © by Oldenbourg Wissenschaftsverlag, München.